The facilitating role of IT systems for legal compliance: the case of port community systems and container Verified Gross Mass (VGM). Issue 1 (2nd January 2019) - Fedi, Laurent; Lavissiere, Alexandre; Russell, Dawn; Swanson, David
ABSTRACT: Regulation and competition create increasing pressure on port logistics. This paper analyzes the influence of information technology solutions during the implementation of new mandatory constraints in port operations, specifically the 2014 mandate by the International Maritime Organization on the container Verified Gross Mass (VGM) to enhance maritime and port safety operations. This research takes a multi-method approach including expert interviews to explore twenty-five case studies of VGM implementation. Expert interviews are transcribed and analyzed with cluster analysis tools to determine recurring themes and insights. Data was collected before, during, and after implementation providing a rigorous study. Findings are threefold. Firstly, the study demonstrates that VGM enforcement entails a significant change in the maritime supply chain, subjecting it to an additional mandatory compliance process in the already complex arena of port operations. Secondly, it shows that structuration of port communities through a strong digitalization of data exchange, such as Port Community Systems (PCS), made easier the transition and the compliance toward a new constraining maritime regulation. Thirdly, this work illustrates that theoretically, PCS not only have positive influence on the adoption of mandatory regulation, but also that communication channels, compatibility and infrastructure are key variables to be managed during implementation.